Mental Health Literacy of Healthcare Providers in Arab Gulf Countries: A Systematic Review - Rowaida Elyamani; Hamed Hammoud (SAGE Publishing, 2020)
Background: The concept of Mental Health Literacy (MHL) relies on our capacity to understand and recognize mental illnesses and the ability to maintain and promote a positive mentality for ourselves and others. In our review, we aim to examine the level of MHL among healthcare providers in the Arab Gulf States. Methods: PubMed, PsycINFO, Medline were searched till August 2019. Studies were included if at least one of the main components of mental health literacy was reported, including (a) knowledge of mental illnesses, (b) stigma toward mental illnesses, (c) confidence in helping patients, and (d) behavior of helping patients, regardless of study design. The risk of bias was rated according to the modified Newcastle-Ottawa Quality Assessment Scale for cross-sectional studies. Results: Seven studies were included in the review; all of them were cross-sectional, with a total of 3516 participants from the healthcare system. Overall most of the studies claimed limited knowledge, negative attitudes, behavior and/or confidence among nurses, pharmacists, and physicians, especially juniors. However, the overall quality of all outcomes was relatively very low. Conclusion: More high-quality evidence and in-depth qualitative studies are required to bridge the gap between mental health needs and services delivered by healthcare providers in the Gulf Arab region.